An analysis of CRM practices in the telecommunication industry in Iraq - Hosam Alden Riyadh; Salsabila Aisyah Alfaiza; Abdulsatar Abduljabbar Sultan; Munadil K. Faaeq; Radyan Dananjoyo (Institute of Advanced Engineering and Science, 2021)
Today, concerning the capacityto react straight for wardly to client demands and offer the client a profound experience that is customized and interactive, organizations in the telecommunication industry must have the capacity toset up, support and continue the connections toward long-term clients. This study attempts to analyze and observe the customer relationship management (CRM) practices that affectfirm performance telecommunication corporations. Thus, the study employed a qualitative method, the primary data were obtained using the questionnaire and the respondents consisted of 100 people. The results propose that customer relationships' management factors included the gathering of information, the processing of data, the management of information, the loyalty of customers, and the retention of customers with significantly related to the performance of a firm in the industry of telecommunication in Iraq.